Eupatilin Impacts on the Progression of Colon Cancer by Mitochondria Dysfunction and Oxidative Stress - Minkyeong Lee; Changwon Yang; Gwonhwa Song; Whasun Lim (MDPI AG, 2021)
Colon cancer is one of the most frequently diagnosed cancer types. Some colon cancer cases resist standard anticancer drugs. Therefore, many studies have focused on developing therapeutic supplements using natural products with low side effects and broad physiological activity. Eupatilin is a flavonoid that is mainly extracted from artemisia and promotes apoptosis in numerous cancer types. However, since the current understanding of its physiological mechanisms on colon cancer cells is insufficient, we investigated how eupatilin affects the growth of two colon cancer cell lines, namely HCT116 and HT29. Our results showed that eupatilin inhibits cell viability and induces apoptosis accompanied by mitochondrial depolarization. It also induces oxidative stress in colon cancer cells and regulates the expression of proteins involved in the endoplasmic reticulum stress and autophagic process. Moreover, eupatilin may target the PI3K/AKT and mitogen-activated protein kinase (MAPK) signaling pathways in colon cancer cells. It also prevents colon cancer cell invasion. Furthermore, eupatilin has a synergistic effect with 5-fluorouracil (5-FU; a standard anticancer drug) on 5-FU-resistant HCT116 cells. These results suggest that eupatilin can be developed as an adjuvant to enhance traditional anticancer drugs in colon cancer.